Progam Kemitraan Masyarakat (PKM) pada Kelompok Usaha Pembuatan Teh Daun Kahumama Berkhasiat Obat di Desa Ondo-Ondolu Kecamatan Batui, Banggai, Sulawesi Tengah - Bahidin Laode Mpapa; Haruni Ode (Jurnal Pengabdian Pada Masyarakat, 2019)
COMMUNITY PARTNERSHIP PROGRAM IN THE BUSINESS GROUP FOR MAKING DRINK KAHUMAMA LEAVES FOR HERBAL IN ONDO-ONDOLU VILLAGE, BATUI DISTRICT, BANGGAI, CENTRAL SULAWESI. The wood of Kahumama includes a lot of local wood in the village of Ondo-Ondolu Batui subdistrict. Partners have the potential to utilize the parts of the kahumama trees such as leaves, to be a product that is worth selling. The potential of leaf raw material is abundant. Suitable business opportunity to utilize the leaves of the Kahumama is a drink efficacious medicine. There are three main problems of the partner, namely: not yet know the process of processing production of kahumama leaves into a tea efficacious medicine; Not yet know the ongoing business and marketing management as well; Not able to overcome the existence of people who still do wood theft in the working area of forest farmer groups. To solve the problem of partners given solutions in the form of training processing production process of Kahumama tea leaves that include: raw material selection techniques, trade, ministry, winding, drying and packaging; Business management and marketing training; and educating people about forests that include forest outcomes, forest cultivation and forest benefits from ecological, social and economic aspects. Community Partnership Program of the business group of the tea making leaves Kahumama efficacious drug implemented for one year in the village Ondo-Ondolu Batui District Banggai. The stages of this program are: observation, production process training of tea processing leaves, business management and marketing training as well as the importance of preserving forests, forest products, forest cultivation and the benefits of forests (ecology, social and Economic development). The result of this community service is farmer group Skills increased in the processing and production of herbal drink Kahumama leaves, thus the welfare of the community increases.